Pengaruh promosi terhadap keputusan pembelian pada era new normal di mangsi tropical denpasar bali - tresnawathi, dayu era; Putra, Agus Muriawan; Suarka, Fanny Maharani (Jurnal Kepariwisataan dan Hospitalitas, 2024)
Mangsi Tropical is a local Balinese coffee brand that produces Arabica coffee from Kintamani. Mangsi Tropical uses social media Instagram as their marketing. By using the Mangsi Tropical account and collaborating with several Instagram accounts in promoting the culinary field. This is done to be able to approach the target market and expand information to customers who are interested in the promotions carried out by Mangsi Tropical. Promotional influence is used as a parameter to determine the impact of success in product promotion. This study aims to determine the marketing promotions that have been carried out by Mangsi Tropical and the effect of promotions on product purchasing decisions in the era new normal at Mangsi Tropical. The sampling technique used purposive sampling method using an online questionnaire to 60 respondents based on the number of consumer visits who came to Mangsi Tropical. The data analysis technique in this research uses simple linear regression analysis. Collecting data through observation, interviews, questionnaires, literature study and documentation The results of the study indicate that the marketing promotion implemented by Mangsi Tropical includes advertising (advertising), sales promotion (sales promotion), public relations (public relations) and direct marketing (direct marketing). The application of promotions has been proven to be able to bring in visitors and increase products from Mangsi Tropical. The effect of promotion on product purchase decisions in the new normal at Mangsi Tropical has a positive and significant effect. This is evidenced by the value of t_hitung 7,891 , t_table 2,001. Based on the value of the coefficient of determination of 0.518, it means that promotion has an influence of 51.8% on product purchase decisions in the new normal at Mangsi Tropical, while the remaining 48.2% are other variables not examined by researchers. Keywords: Promotion, Product Purchase Decision, Mangsi Tropical